De-Regulation of Criminal Law Provisions in Regional Regulations after the Criminal Codes Enactment - Jamaludin, Ahmad (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Indonesia has various criminal provisions within the regional regulatory framework which cover many articles. In connection with this, the enactment of Law No. 1 of 2023 concerning the Criminal Code in 2025 will ensure compliance with all criminal regulations stipulated in regional regulations with statutory provisions. In this regard, the implementation of Law No. 1 of 2023 concerning the Criminal Code (KUHP), which is scheduled to come into effect in 2025, guarantees the submission of all criminal laws outlined in regional regulations to the provisions of that law. The aim of this research is to examine the existence of the terms crime and violation as well as the provisions for criminal sanctions in the existing regional regulatory framework after the enactment of Law No. 1 in 2023. This research uses a normative juridical methodology, using a statutory approach and a conceptual approach. This research concludes that to prevent disruption of legal harmonization in Regional Regulations, it is necessary to revise the legal provisions contained in Law No. 23 of 2014 concerning Regional Government and Law No. 12 of 2011 concerning the Formation of Legislative Regulations, in order to overcome potential ambiguity. Besides that, it is very important for the Regional Government to carry out a comprehensive inventory and evaluation of regional regulations that use the terms